Influence of the prehospital administered dosage of epinephrine on the plasma levels of catecholamines in patients with out-of-hospital cardiac arrest. Issue 8 (August 2021) - Nakajima, Jun; Sawada, Yusuke; Isshiki, Yuta; Ichikawa, Yumi; Fukushima, Kazunori; Aramaki, Yuto; Oshima, Kiyohiro
Abstract: Aim: This study evaluated whether the prehospital administered dosage of epinephrine (Ep) influences the plasma levels of catecholamines in patients with out-of-hospital cardiac arrest (OHCA). Methods: This was a prospective, observational clinical study. Patients with OHCA transferred to our hospital between July 2014 and July 2017 were analyzed. The plasma levels of catecholamines were measured using blood samples obtained immediately upon arrival at the hospital and before the administration of Ep. Patients were divided into three groups based on the prehospital administered dosage of Ep: no prehospital administration (group Z); 1 mg of Ep (group O); and 2 mg of Ep (group T). The levels of catecholamines, as well as the conditions of resuscitation prior to and after arrival at the hospital were compared between the three groups. Results: We analyzed 145 patients with OHCA (96, 38, and 11 patients in groups Z, O, and T, respectively). Group T exhibited the highest plasma levels of Ep with a statistically significant difference, however, there were no significant differences in the plasma levels of norepinephrine (Nep), dopamine (DOA) and vasopressin (ADH) among the three groups. Conclusion: The prehospital administered dosage of Ep influences the plasma levels of Ep; however, it does not contribute to the plasma levels of Nep, DOA and ADH in patients with OHCA. Abstract : Epinephrine, Cardiopulmonary arrest, Cardiopulmonary resuscitation